2017
DOI: 10.1140/epjc/s10052-017-4785-x
|View full text |Cite
|
Sign up to set email alerts
|

Unified cosmology with scalar–tensor theory of gravity

Abstract: Unlike the Noether symmetry, a metric independent general conserved current exists for non-minimally coupled scalar-tensor theory of gravity if the trace of the energymomentum tensor vanishes. Thus, in the context of cosmology, a symmetry exists both in the early vacuum and radiation dominated era. For slow roll, symmetry is sacrificed, but at the end of early inflation, such a symmetry leads to a Friedmann-like radiation era. Late-time cosmic acceleration in the matter dominated era is realized in the absence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 85 publications
1
59
0
Order By: Relevance
“…Hence techniques from Classical Mechanics can be applied for the determination of conservation laws and the derivation of solutions. Indeed various approaches have been applied in the literature [61,66,[71][72][73][74].…”
Section: Integrabilitymentioning
confidence: 99%
“…Hence techniques from Classical Mechanics can be applied for the determination of conservation laws and the derivation of solutions. Indeed various approaches have been applied in the literature [61,66,[71][72][73][74].…”
Section: Integrabilitymentioning
confidence: 99%
“…Finally, C αβ (x, t) is transverse and trace-free (C β α|β = 0 = C α α ) and corresponds to the tensor-type perturbation. Indices are based on g (3) αβ as the metric and the vertical bar ('|') indicates a covariant derivative. Now, we decompose the energy-momentum tensor along with the scalar field by introducing perturbation as, T a b (x, t) =T a b (t) + δT a b (x, t), φ(x, t) =φ(t) + δφ(x, t), and F =F + δF .…”
Section: Gravitational Perturbation: Validating the Relation Between mentioning
confidence: 99%
“…Although, perturbatively it encounters ghost degrees of freedom, non-perturbatively it is well behaved. Further, although unification of the early inflation with late-time cosmic acceleration with non-minimally coupled scalar field has recently been achieved [3], nevertheless one can't ignore the presence of higher order terms in the early universe, particularly because inflation without phase transition is an essential feature of such higher order term [4,5]. Now, in the homogeneous and isotropic background, R 2 µν and R 2 terms differ only by a total derivative term, and it is therefore sufficient to add scalar curvature squared term to the above action, which therefore reads as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horndeski' theory [32] presents the most general scalar-tensor theory of gravity ensuring no more than second-order field equations to avoid ghost instability due to Ostrogradski theorem. Recently, in view of a general conserved current, obtained under suitable manipulation of the field Equations [33][34][35][36], a non-minimally coupled scalar-tensor theory of gravity, being a special case of Horndeski' model, has been studied extensively in connection with the cosmological evolution, starting from the very early stage (Inflationary regime) to the late-stage (presently accelerated matter-dominated era) via a radiation dominated era [37]. It has been found that such a theory admits a viable inflationary regime, since the inflationary parameters viz.…”
Section: Introductionmentioning
confidence: 99%